Cosmology with mass dimension one fields: recent developments - Pereira, S. H. [UNESP]; Lima, R. de C. [UNESP]; Alves, M. E.S. [UNESP]; Guimarães, T. M.; Jesus, J. F. [UNESP]; Souza, A. P.S. (Springer Nature, 2020)
The recent developments with mass dimension one fermionic fields in a cosmological context are briefly presented. The main results for inflation, dark matter, dark energy, cosmological perturbations, particle creation and interacting models are discussed. The Friedmann–Robertson–Walker equations for both torsion and torsion free cases are compared and discussed in different scenarios. We review and call attention for some important assumptions made on derivation of the motion equations. Other approaches and generalizations are suggested and some limitations are presented.